Comparative Analysis of Compatibility Effects on Invigorating Blood Circulation for Cyperi Rhizoma Series of Herb Pairs Using Untargeted Metabolomics - Liu, Pei; Shang, Er-Xin; Zhu, Yue; Yu, Jin-Gao; Qian, Da-Wei; Duan, Jin-Ao (Frontiers in Pharmacology, 2017)
The mutual-assistance compatibility of Cyperi Rhizoma (Xiangfu, XF) and Angelicae Sinensis Radix (Danggui, DG), Chuanxiong Rhizoma (Chuanxiong, CX), Paeoniae Radix Alba (Baishao, BS), or Corydalis Rhizoma (Yanhusuo, YH), found in a traditional Chinese medicine (TCM) named Xiang-Fu-Si-Wu Decoction (XFSWD), can produce synergistic and promoting blood effects. Nowadays, XFSWD has been proved to be effective in activating blood circulation and dissipating blood stasis. However, the role of the herb pairs synergistic effects in the formula were poorly understood. In order to quantitatively assess the compatibility effects of herb pairs, mass spectrometry-based untargeted metabolomics studies were performed. The plasma and urine metabolic profiles of acute blood stasis rats induced by adrenaline hydrochloride and ice water and administered with Cyperi Rhizoma—Angelicae Sinensis Radix (XD), Cyperi Rhizoma—Chuanxiong Rhizoma (XC), Cyperi Rhizoma—Paeoniae Radix Alba (XB), Cyperi Rhizoma—Corydalis Rhizoma (XY) were compared. Relative peak area of identified metabolites was calculated and principal component analysis (PCA) score plot from the potential markers was used to visualize the overall differences. Then, the metabolites results were used with biochemistry indicators and genes expression values as parameters to quantitatively evaluate the compatibility effects of XF series of herb pairs by PCA and correlation analysis. The collective results indicated that the four XF herb pairs regulated glycerophospholipid metabolism, steroid hormone biosynthesis and arachidonic acid metabolism pathway. XD was more prominent in regulating the blood stasis during the four XF herb pairs. This study demonstrated that metabolomics was a useful tool to efficacy evaluation and compatibility effects of TCM elucidation.